Review on Types and Methods of Electroplating on Metals - Saher Mahmood Jawd; Noorhan Ali Hamza, Amal Saadoon Majeed (Journal of Power Electronics and Devices, 2021)
The concepts of electroplating and surface coating are confused. The term paint is generally used when its purpose is aesthetic and decorative, while the term coating is used when it is used for other specific purposes, although the inks used in printing are considered as a cladding process even though they have cosmetic and illustrative purposes as well. Paint is a surface coating material and the surface is coated with it while it is in a liquid suspension by one of the appropriate methods such as brush, roller brush, spray, or electrostatic deposition. Then the paint dries, or, more properly, the coating layer turns from liquid to solid, and this layer covers the surface completely and is generally a few tens of micrometers thick. Surfaces are used for two purposes: to protect and decorate., As an application of the electroplating process, plating using copper metal for silver plating was widespread and adopted globally, and in the period between 1840 and 1841 AD, the electroplating process was used in the economic field, and then this process has applications for large and growing industries using advanced equipment.